Combined Effects of Allee Effect and Hyperbolic Mortality on Predator-Prey System - Sahoo, Kalyanashis; Sahoo, Banshidhar (Journal of Applied Nonlinear Dynamics, 2026)
The predator-prey system with additive Allee effect in the growth rate of prey is proposed and studied. The proposed system is extended by introducing hyperbolic mortality rate for top predator instead of using common linear mortality rate. The system is analysed in terms of both analytical and numerical aspects. The model system demonstrates that when the system's parameters are changed, it exhibits both stable and unstable dynamics. The Hopf point bifurcation is also studied in the proposed system. The study enhances dependence of the system's dynamics on Allee effect and other crucial parameters. The discipline of forestry and natural ecology can benefit from the findings and experience gained from this study.